B-SIGHT: Business Intelligence Tool for Online Home-Based Entrepreneurs - Zakir Ali, Zulaikha Nurbatrisyia (IRC, 2020)
This paper focus on the study on the problem and issue faced by the online home-based business entrepreneurs in handling and recording their historical business data. The scope of study is mainly focusing on the online home-based business owner in Malaysia that uses the social media sites as a platform to promote and conduct their business. This further justify through review of literature on the characteristics of a home-based business, the importance of using data for business growth and the overview of business intelligence tools. Methodology conducted throughout the project is agile method that is divided into planning, analysis and requirement gathering, designing and documenting data, development of prototype and also the evaluation stage. As a result, this project paper presents a business intelligence application that can support online home-based business entrepreneur in Malaysia through presenting a business performance report from business data analysis.